When FUE goes wrong! - Arvind Poswal; Sangay Bhutia; Ruby Mehta (Wolters Kluwer Medknow Publications, 2011)
Follicular unit extraction (FUE) is an accepted method of extracting individual follicular unit grafts for hair transplant surgery. Since follicles are harvested from the back of the scalp using tiny punches resulting in minimal scarring, it has gained rapid acceptance among the patients. However, due care needs to be exercised while performing FUE. FUE should not be confused with the older plug graft extraction methods of coring out hair-bearing skin plugs. Lack of due diligence while performing such extractions can lead to subluxation of the grafts into the subdermal layer of scalp. Overtumescence of the scalp donor area, use of blunt punches and trying to "core" out the full thickness grafts can all contribute to this. The following cases illustrate some pitfalls to be avoided while performing FUE and the adverse consequences if they occur.